(3GdMeGjI GdbGfhfjI ddJUejeGJ GdeYeGQjI (B: s (3OQGSI ebGQfI (B/ s - (3YHO Gddg eMeO fhQ GdOjf YHO Gddgs; (3eMeO SGej YHO GdUGObs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2020)
(3JYO afhf GdYeGQI CMO CbOe CfhGY Gdafhf GdJi YQaJgG GdHTQjI(B: (3h HbOQ GQJHGW GdYeGQI HGdaf aEfgG JQJHW CjVG HMbhb GdedcjI GdacQjI GQJHGWG hKjbG(B: (3HGYJHGQgG (B- (3ai GdebGe GdChd (B- (3EMOi UhQ GdEHOGYGJ GdPgfjI(B: (3ShGA GdafjI Ch GdUfGYjI; h dbO oCOQLJ GdJUejeGJ GdeYeGQjI Vef GdCYeGd GdPgfjI GdeTehdI HMeGjI JTQjYGJ Mbhb GdedcjI GdacQjI(B: (3ShGA CcGf Pdc ef NdGd GdGJaGbjGJ GdOhdjI Ce GdJTQjYGJ GdhWfjI(B. (3JYJHQ gPg GdOQGSI eMGhdI fMh GdJYQa Ydi GdCYeGd GdeYeGQjI GdLOjQI HGdMeGjI h JcjjagG bGfhkfG(B: (3ceG Jdbi GdVhA Ydi GdMbhb GdJi jcJSHgG GdeYeGQjhf Ydi EHOGYGJge GdPgfjI(B: (3HGdEVGaI Edi GdGSJKfGAGJ h GdbjhO GdhGQOI Ydi Jdc GdMbhb h VhGHW EYeGdgG; hdbO MGhdfG (B- (3ef NdGd gPg GdOQGSI (B- (3GSJjVGM h HjGf GdJMOjGJ GdJi bO JMhd Ohf EYeGd Ch JWHjb GdMeGjI GdbGfhfjI Ydi GdJUejeGJ GdeYeGQjI(B: (3h Pdc fXkQG ddWHjYI GdNGUI GdJi JJSe HgG GdJUejeGJ GdeYeGQjI h GNJdGagG Yf HGbi GdEHOGYGJ GdPgfjI GdCNQi(B. (3h bO QCjfG ef GdefGSH Cf JfUQa gPg GdOQGSI fMh JHUjQ QLGd GdbGfhf(B: (3h cPdc GdeYeGQjhf(B: (3HGdLhGfH GdbGfhfjI GdJi JMce MeGjI GdJUejeGJ GdeYeGQjI hakbG dBdjGJ Mbhb GdedcjI GdacQjI GdeNJdaI(B: (3cd Pdc ai EWGQ ef GdebGQfI GdJi JYcS ChLg GdTHg h GdGNJdGa Hjf GdfXGejf GdbGfhfjjf GdaQfSi h GdeUQi(B: (3ef CLd GdhUhd Edi fXGe bGfhfi CcKQ JcGekdG dMeGjI GdeYeGQjjf h GdeMGaXI Ydi Mbhbge GdNGUI HEHOGYGJge GdPgfjIs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2020.s
(3HHdjhLQGajG(B: (3UaMGJ (B673-722.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdaQfSjI hGdYQHjI(B.s
Keywords: (3GdeSDhdjI GdeYeGQjIs; (3Mbhb GdedcjI GdacQjIs; (3GdJUejeGJ GdeYeGQjIs; (3GdeUfa GdeYeGQj s; (3GdeDda GdeYeGQj s; (3GdMbhb GdCOHjI ddeDdajf GdeYeGQjjf GdTQcGAs; (3GdMbhb GdeGdjI ddeDdajf GdeYeGQjjf GdTQcGA s; (3GdMeGjI GdbGfhfjIs; (3GdGTJQGc GdJGe s; (3GdGTJQGc GdfGbU s; (3GdeUfaGJ GdeYeGQjI GdLeGYjI s; (3GdeUfaGJ GdeYeGQjI GdeTJbI s; (3GdMeGjI GdLfGFjI ddJUejeGJ GdeYeGQjIs; (3GdMeGjI GdeOfjI ddJUejeGJ GdeYeGQjI s; (3GdfeGPL GdUfGYjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs